Aquaculture Impacts on China’s Marine Wild Fisheries Over the Past 30 Years - Zhao, Kangshun; Zhang, Min; Wang, Kang; Zhu, Konghao; Xu, Congjun; Xie, Jiayi; Xu, Jun (Frontiers in Marine Science, 2021)
China is the world’s largest producer of aquaculture and capture fisheries. How this country develops its aquaculture sector and whether such development can relieve pressure on wild fisheries remain a contentious issue in the past and for the future. This study aims to provide a broad assessment on the impact of aquaculture development in different periods on marine wild fisheries on the basis of aquaculture and marine wild fish catch data from all the coastal provinces of China. China’s aquaculture and capture fisheries have undergone substantial changes. From 1989 to 2002, China’s aquaculture, especially mariculture, had a strong relationship with marine wild fisheries. However, from 2003 to 2018, the impact of mariculture was weakened, whereas that of freshwater aquaculture had increased. Although aquaculture still puts pressure on marine wild fisheries, China’s aquaculture is currently moving toward sustainable development pattern with low input and high output. These results provide the first statistical evidence on the effects of aquaculture development on marine wild fisheries and contribute to the sustainable management of China’s aquaculture and marine capture fisheries.